Marfan Syndroma in Ophthalmology – case report - Janicijevic Petrovic, Mirjana Andreja (PONS - medicinski časopis, 2013)
Abstract Purpose Authors report the case of a 59-year old woman with bilateral posterior lens luxation in vitreous, medically controlled glaucoma and corneal adherent leucoma with vascularization in whom Marfan syndrome was diagnosed. Methods The patient underwent complete clinical eye and systemic examinations and blood samples were drawn for mutational screening of fibrillin1 gene (FBN1). Conclusion The patient was diagnosed with Marfan syndrome on clinical basis do to genetic testing revealed a new heterozygous mutation in the FBN1 gene and described with ocular signs. The patient required pars plane vitrectomy with lensectomy, or Ahmed valve implantation in vitreous to control glaucoma secondary, but the finally treatment was without surgical modules from recommendation of referent expert team. In our patient glaucoma secondary was under therapy control. Keywords: Marfan syndroma, lens dislocation, genetic, diagnosis, therapy